2019
DOI: 10.1037/xge0000623
|View full text |Cite
|
Sign up to set email alerts
|

Establishing construct validity evidence for regional measures of explicit and implicit racial bias.

Abstract: Large-scale data collection has enabled social scientists to examine psychological constructs at broad, regional levels. However, because constructs and their measures initially operationalized at the individual level may have qualitatively and quantitatively different properties at other levels of analysis, the validity of constructs must be established when they are operationalized at new levels. To this end, the current research presents evidence of construct validity for explicit and implicit racial bias a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 72 publications
(167 reference statements)
9
134
0
Order By: Relevance
“…Payne et al () reviewed empirical evidence showing that effects at the individual level are generally unstable (Gawronski, Morrison, Phills, & Galdi, ) and only weakly associated with individual differences (e.g., in predicting discriminatory behaviors; Greenwald et al, ; Oswald et al, ). On the contrary, at the aggregate level (e.g., IAT scores aggregated as a function of US states), these effects are stable (Payne et al, ; see also Hehman, Calanchini, Flake, & Leitner, ) and strongly associated with situational variables (e.g., city‐level; Zerhouni et al, ; region‐level; Hehman et al, ; county/state‐level; Orchard & Price, ; Payne et al, ). Authors concluded that these effects would be mostly due to the situational accessibility of concepts (i.e., conveyed by racist institutions and cultures), what the authors called the “systemic bias”.…”
Section: Discussionmentioning
confidence: 99%
“…Payne et al () reviewed empirical evidence showing that effects at the individual level are generally unstable (Gawronski, Morrison, Phills, & Galdi, ) and only weakly associated with individual differences (e.g., in predicting discriminatory behaviors; Greenwald et al, ; Oswald et al, ). On the contrary, at the aggregate level (e.g., IAT scores aggregated as a function of US states), these effects are stable (Payne et al, ; see also Hehman, Calanchini, Flake, & Leitner, ) and strongly associated with situational variables (e.g., city‐level; Zerhouni et al, ; region‐level; Hehman et al, ; county/state‐level; Orchard & Price, ; Payne et al, ). Authors concluded that these effects would be mostly due to the situational accessibility of concepts (i.e., conveyed by racist institutions and cultures), what the authors called the “systemic bias”.…”
Section: Discussionmentioning
confidence: 99%
“…See Hehman et al . () for discussion of pertinent psychometric questions about these studies and their novel approach to the use of implicit measures.…”
mentioning
confidence: 99%
“…We used both the implicit and explicit measures to estimate the size of ideological differences and similarities on these attitudes. At the aggregate level, there tends to be a strong relationship between implicit and explicit attitudes (Hehman, Calanchini, Flake, & Leitner, 2019)-suggesting our analyses, which are also at an aggregate level, should produce similar trends for both types of measures.…”
Section: Datamentioning
confidence: 63%